2010
DOI: 10.1080/15459624.2010.486693
|View full text |Cite
|
Sign up to set email alerts
|

Workers’ Experience of Slipping in U.S. Limited-Service Restaurants

Abstract: The leading cause of injuries among restaurant workers is same-level falls, a significant proportion of which result from slipping. This study examines the experience of limited-service restaurant workers with slipping, their use of slip-resistant shoes, and their floor-cleaning practices. A total of 475 workers from 36 limited-service restaurants in six U.S. states participated in a 12-week prospective cohort study on slipping in the workplace. At baseline, participants completed a survey that gathered inform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 19 publications
2
19
0
1
Order By: Relevance
“…In addition, proper executions of existing cleaning protocols could affect the outcome. Verma et al (2010) reported that 62% of the participants who were responsible for cleaning floors used hot/warm water with widely used enzyme-based floor cleaners, thus violating the manufacturer’s cold water floor cleaning protocol. Quirion, Poirier, and Lehane (2008) used very limited cleaning methods with few cleaning chemicals in their experiment.…”
Section: Tribologymentioning
confidence: 99%
“…In addition, proper executions of existing cleaning protocols could affect the outcome. Verma et al (2010) reported that 62% of the participants who were responsible for cleaning floors used hot/warm water with widely used enzyme-based floor cleaners, thus violating the manufacturer’s cold water floor cleaning protocol. Quirion, Poirier, and Lehane (2008) used very limited cleaning methods with few cleaning chemicals in their experiment.…”
Section: Tribologymentioning
confidence: 99%
“…Floor surface contamination is frequently reported when slips occur 15 23. Although regular effective floor cleaning to reduce floor contamination may reduce the incidence of slipping, the process of cleaning itself, such as when the floor is wet during and after mopping, can also present a slipping hazard.…”
mentioning
confidence: 99%
“…They further calculated that the total workers' compensation losses caused by same-level falls in restaurants resulted in an industry-wide cost of US$116 per worker, annually. Verma et al 24 previously reported that participants working in restaurants where shoes were not provided by the employer reported paying a mean of US$29.26 (SD 10.82) for slip-resistant shoes. Based on these findings, even without adjusting for inflation, each pair of slip-resistant shoes would result in cost savings of about US$58 (116/2), assuming 50% reduction in injuries from same-level falls in workers' compensation cost alone.…”
Section: Discussionmentioning
confidence: 99%
“…The survey materials were made available in three languages: English, Spanish and Portuguese. Enrolment procedures have been previously described in detail 22 24…”
Section: Methodsmentioning
confidence: 99%